PENERAPAN STRATEGI DIRECTED READING THINKING ACTIVITY (DRTA) UNTUK MENINGKATKAN UNSUR INTRINSIK CERITA ANAK BAGI SISWA KELAS V SD NEGERI 66 HARAPAN BARU - Radesmi Radesmi; Erlisnawati Erlisnawati; Syahrifuddin Syahrifuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :The problem in this research is the result of Indonesian students studying in class five (V) SDN 66 Harapan Baru is still low with an average value of 40.35 (with KKM 65). The purpose of this research is to improve the learning outcomes of students in grade five (V) SDN 66 Harapan Baru with the implementation of strategies directed reading thinking activity. This research is a class act with two cycles in the second half of 2014/2015. Before the implementation of the strategy directed reading thinking activity average value of 40.35, after the application of the strategy directed reading thinking I was 61.49 UH activity increased 52.39% from the base score with an average of 40.35. UH II is 76.87 which increased 90.5%. Teacher activity with penerapann strtegi directed reading thinking activity in the first meeting of the first cycle was 45.83% (less category), and the second meeting was 62.5% (medium category) in the meeting to two rising 16.67 points. In the second cycle, the activities of teachers in the first meeting was 79.16 (good category) increased 16.66 points from the second meeting of the first cycle. Teacher activity became 91.66% (excellent category) at the second meeting, which is an increase of 12.5 points. Activity of students in the first meeting of the first cycle was 50% (medium category), and 62.5% (medium category) in the second meeting, which improved 12.5 points. In the second cycle, the activity of students in the first meeting was 83.33% (both categories) increased 20.83 points from the second meeting of the first cycle. The second meeting of the second cycle was 91.66% excellent category) increased 8.33 points. Implementation of strategies directed reading thinking activity (DRTA) can improve learning outcomes Indonesian understand the intrinsic elements of a children's story to fifth grade students of SDN 66 Harapan Baru.Keywords : Strategies Directed Reading Thinking Activity (DRTA), Indonesian Learning Outcomes